2020
DOI: 10.1007/s00415-020-09841-0
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in early MS: contribution of white matter lesions, deep grey matter atrophy, and cortical atrophy

Abstract: Background Cognitive impairment (CI) is a frequent and debilitating symptom in MS. To better understand the neural bases of CI in MS, this magnetic resonance imaging (MRI) study aimed to identify and quantify related structural brain changes and to investigate their relation to each other. Methods We studied 51 patients with CI and 391 patients with cognitive preservation (CP). We analyzed three-dimensional T1-weighted and FLAIR scans at 3 Tesla. We determined mean cortical thickness as well as volumes of cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…Brain atrophy results from years of chronic inflammation and axonal degeneration on top of physiological brain volume loss with age. However, it is also already found early in MS ( 74 77 ) but is most pronounced with disease duration ( 78 , 79 ). It is reported to correlate more closely with the clinical impairment than the T1 or T2 lesion load in the white matter and identifies patients at risk for progression ( 80 ), making it an important MRI biomarker ( 81 , 82 ).…”
Section: Discussionmentioning
confidence: 90%
“…Brain atrophy results from years of chronic inflammation and axonal degeneration on top of physiological brain volume loss with age. However, it is also already found early in MS ( 74 77 ) but is most pronounced with disease duration ( 78 , 79 ). It is reported to correlate more closely with the clinical impairment than the T1 or T2 lesion load in the white matter and identifies patients at risk for progression ( 80 ), making it an important MRI biomarker ( 81 , 82 ).…”
Section: Discussionmentioning
confidence: 90%
“…The role of white matter (WM) focal lesions as correlates of global cognitive impairment or deficit in specific cognitive functions has been widely explored in MS. Initial findings from cross-sectional studies [ 15 , 16 ] have been confirmed by longitudinal reports highlighting the role of short-term lesion load changes in predicting cognitive performance at follow-up [ 17 , 18 , 19 ], but evidence remains contradictory [ 16 ]. Although it is not possible to directly compare studies conducted with different designs in different populations, the overall emerging message is that demyelinating lesions play a minor role in comparison with atrophy and normal appearing tissue damage [ 20 , 21 ].…”
Section: Structural Correlates Of Cognitive Impairmentmentioning
confidence: 99%
“…In particular, thalamus and other deep GM structural changes play an important role in the development of the full spectrum of cognitive impairment in MS [ 3 , 31 , 80 , 81 , 82 ], including attention-processing speed, executive function, fluency, visuo-spatial working memory and verbal memory [ 80 , 83 ]. Thalamic atrophy, induced by the interplay of local and remote pathologic processes [ 84 , 85 ], has been associated with cognitive impairment from the early stages of MS and could further enhance cognitive changes in patients with more pronounced WM lesion load [ 15 ]. During the course of the disease, the progression of cognitive changes mirrors deep GM volume changes, suggesting a direct association [ 77 ].…”
Section: Structural Correlates Of Cognitive Impairmentmentioning
confidence: 99%
“…The evolution of cognitive deterioration, which can occur from a very early stage of the disease, 130 is weakly associated with the inflammatory disease activity as measured by the accrual of new/enlarging T2w lesions. 131 , 132 By using functional MRI or DTI, it has been demonstrated that cognitive impairment is better accounted for by the subtle worsening of grey matter pathology, and by network disruption and axonal degeneration, irrespective of inflammatory changes. 133 …”
Section: Future Directionsmentioning
confidence: 99%